CHANGE ORDER DAN RISIKO CHANGE ORDER PADA PROYEK JALAN DI JAWA BARAT - Mega Waty; Hendrik Sulistio (Program Studi Teknik Sipil, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2021)
Change Order is a change that occurs in a construction project and cannot be avoided. Analysis of change orders on 10 West Java road construction projects examines how causes of change orders vary between upgrade projects versus maintenance projects, and types of construction (e.g. asphalt works, drainage, structures, and widening of road shoulders and grained pavements, restoration of conditions and minor works and daily work). This study also examines the risks posed by change orders by measuring the frequency and average percentage changes in project costs for various types of change orders. The research methodology is by looking for real data on road construction projects from 2014-2018. The result is that the main causes of change orders are consistently terminated contracts, owner-induced increases, and swelling of contract items, and contract negligence. The risk of a change order is the highest in the work: Hot Asphalt Mixture, Class S Upper, Laston Wear, Stonework, Class B Upper Base, Cement Concrete Pavement, Low quality f'c 15 MPa Concrete, Stone Pairs with Mortar, Embankment Choice, Thermoplastic Road Markings.